Resection of ruptured aneurysm associated with bilateral anomalous posterior inferior cerebellar anastomotic arteries: case report and review of literature - Han, Qingdong; Wang, Zongqi; Liu, Tong; Huang, Yabo (Frontiers in Neurology, 2023)
Introduction Aneurysms on the posterior inferior cerebellar artery (PICA) may not be the major part of intracranial aneurysm. Especially, an aneurysm located on the bilateral posterior inferior cerebellar anastomotic artery has abnormal anatomical characteristics in the vessel wall and then causes stroke including subarachnoid hemorrhage. This case report explores the direct resection of a ruptured aneurysm associated with the bilateral anomalous anastomotic artery of PICA. Methods The case report discusses a 53-year-old woman who suffered from sudden severe headache and vomiting for more than 3 h admitted to our hospital. Emergency computed tomography (CT) revealed subarachnoid hemorrhage (SAH) in the third and fourth ventricles. Preoperative 3 Dimensions-digital subtraction angiography (3-D DSA) indicated a ruptured aneurysm located on the bilateral posterior inferior cerebellar anastomotic artery. Postoperative pathological findings indicated the characteristics of parent artery PICA and control aneurysm. The authors performed an overview of PICA aneurysms with anomalous variation in the Pubmed, Web of Science, and Medline databases. The search was until 1 August 2023. Related terms “posterior inferior cerebellar artery” And “aneurysm” AND “anatomical variants” were used to search the review. The reasons for anomalous variation anastomosis between bilateral PICAs were analyzed. Results The aneurysm was resected successfully. Post-operative 3-D DSA revealed the disappearance of the aneurysm. The vessel wall of anastomotic PICA showed neovascularized hyperplasia, abnormal arrangement of smooth muscle, CD31+ endothelial cells, and SMA+ smooth muscle cells. In contrast, when it came to aneurysm, the wall at the location of the fracture thinned, which could be used to explain that the local nodular protrusion was formed and CD31+ endothelial cells existed. No neurological deficits were found at her 1-year follow-up visit (mRS score of 0). Conclusion Direct resection of ruptured aneurysm associated with bilateral anomalous posterior inferior cerebellar anastomotic arteries was an effective treatment and careful consideration of the anatomical characteristics concerning the interesting aneurysm and the variant PICA was critical for sate treatment. Also, the literature on the lesion was reviewed.